NH3 spatiotemporal variability over Paris, Mexico City, and Toronto, and its link to PM2.5 during pollution events - C. Viatte; R. Abeed; S. Yamanouchi; S. Yamanouchi; W. C. Porter; S. Safieddine; M. Van Damme; M. Van Damme; L. Clarisse; B. Herrera; B. Herrera; M. Grutter; et al. (Atmospheric Chemistry and Physics, 2022)
Megacities can experience high levels of fine particulate matter (PM2.5) pollution linked to ammonia (NH3) mainly emitted from agricultural activities. Here, we investigate such pollution in the cities of Paris, Mexico, and Toronto, each of which have distinct emission sources, agricultural regulations, and topography. Ten years of measurements from the infrared atmospheric sounding interferometer (IASI) are used to assess the spatiotemporal NH3 variability over and around the three cities.